Is the dark triad always detrimental to firm performance? Testing different performance outcomes and the moderating effects of competitive rivalry - Haar, Jarrod; de Jong, Kirsty (Frontiers in Psychology, 2023)
There is growing evidence that CEOs who have the ‘dark triad’ of personality traits (Machiavellianism, narcissism, and psychopathy) detrimentally influence firm performance. However, there is still much we do not know. The present study suggests that the CEO dark triad might directly influence typical performance indicators in different ways: positively affecting external performance indicators (breakthrough sales), but negatively affecting internal performance indicators (organizational performance). We argue that the CEO dark triad can be interpreted differently by those external to the firm versus internally, where managers are much closer to the CEO’s dark personality. Our model includes managerial capital as a mediator and competitive rivalry as a moderator, and ultimately tests a moderated mediation model. Using data from 840 New Zealand firms, we find that the dark triad links to outcomes, as expected. While the CEO dark triad is negatively related to managerial capital, managerial capital does positively predict both performance indicators, and partially mediates the CEO dark triad effect. Overall, moderating effects highlight that the CEO dark triad is less detrimental in fiercely competitive business environments, acting as a consistent boundary condition across models. As competitive rivalry increases, the indirect effect of the CEO dark triad on performance decreases. We discuss the implications for understanding the role that the CEO dark triad can play in firms.